Proporsi Potongan Utama Komersial Karkas (Primal Cut) Pada Sapi Brahman Cross - Amri, Ulil (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2009)
The experiments was conducted to find proportion of primal cut on Brahman Cross Carcass. The experiment was conducted for 6 months in Slaughter house PT.SampiCo Adhi Abbatoir Cibitung Bekasi  West  Java.  A  hundred  forty  nine  (imported  from  Australia)  castrated  Brahman  Cross  cattle (steer) were used with 1.5 up to more than 4 years of age and 379 – 622 kg of body weight. The design was randomized block completely design in 3 x 4 factorial design with 3 feedlots and 4 group of body weight and was analysed following GLM procedure with median of smallest quadrat (SAS, 1985 and Montgomery,  1991).  The  study  showed  that  there  was no  significant  on  primal  cut  weight  and  its  percentage  among  feedlot.  Increase  body  weight  significantly  increased  weight  of  primal  cut  but  no proportion of primal cut.